Corporative Ecological System and Processes Mathematical Modelling - Kozulia, T. V.; Sharonova, Natalia Valeriyevna (Харківський національний університет радіоелектроніки, 2009)
In the article the basics of the corporate approach in the system of ecological monitoring for solving of ecological problems tasks macro- and a microlevel are considered. Practical results of realization of corporate system in definition of an ecological estimation of processes in the soils are submitted.
Keywords: corporative system; ecological monitoring; entropy; information; thermodynamic function